Hoop strain measurement during a SiC/SiC ceramic composite tube burst test by digital volume correlation of X-ray computed tomographs - Zhao, S; Chen, Y; Saucedo-Mora, L; Connolley, T; Marrow, TJ (Springer, 2022)
Background: Silicon carbide-fibre/silicon carbide matrix (SiC/SiC) composites are candidate materials for accident tolerant fuel cladding in light water and advanced gas cooled nuclear fission reactors. The mechanical and damage behaviour of ceramic composites is sensitive to the composite geometry, the microstructure and the loading state. Reliable test methods are needed to investigate the subcritical damage that affects hermetic properties and strength, and this requires precise measurements under loading states that are representative of operating conditions. Objective: The objective was a novel methodology to measure the deformation of an internally pressurised ceramic composite tube. Methods: A burst test of an internally ground SiC/SiC (filament wound and braided) ceramic composite tube, pressurized by radial expansion of a compressed elastomer insert, was observed in situ by high resolution (synchrotron) X-ray tomography. The full field three-dimensional displacements were measured by digital volume correlation, with a precise rotation correction applied to obtain the relative radial and circumferential displacements of the tube wall for the first time. Results: The hoop strain, and its spatial variations, were determined as a function of the applied hoop stress and showed ovalisation and barreling of the tube. The quantity of subcritical matrix cracking increased with the tensile hoop strain, but the critical crack that caused rupture was not at the location of maximum tensile strain. Conclusion: Precise measurements of the deformation during the burst test found non-uniform hoop strains that caused a non-uniform distribution of subcritical cracking, which could influence the hermetic properties and strength.